Pengaruh Laba Antar Divisi, Pajak, Dan Tunneling Incentive Pada Keputusan Transfer Pricing Perusahaan Manufaktur Terbuka - Abubakar Arif; Wida Cintya Dewi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2012)
Transfer Pricing is a price transaction happened between companies with special relationship. Transfer pricing phenomenon could happened is based on the management motivation in order to tax avoidance or any opportunistic behaviour, especially to do wealth transfer among related parties. For multinational corporate view, transfer pricing is one of the effective strategies to compete with their competitors. The aim of this research is to test the influence of profit among division, taxes, and tunneling incentive on transfer pricing decision in manufacture companies that listed at Indonesia Stock Exchange. Sample selection was using purposive sampling with final sample 95 companies and 243 observationa from 2009-2012 the result shows that profit among division and tunneling have an influence on transfer pricing decision, while taxes have not influence on transfer pricing decision.This is due a business decision driven by economic fundamentals such as rate of return and not the tax considerations. The findings give any opportunity to the next researchers to investigate the effect of other variables on transfer pricing decision, such as bonus scheme that based on income.